2012
DOI: 10.2478/s13540-012-0022-3
|View full text |Cite|
|
Sign up to set email alerts
|

The mean value theorems and a Nagumo-type uniqueness theorem for Caputo’s fractional calculus

Abstract: Dedicated to the memory of my teacher, Professor Dr. Helmut BraßWe generalize the classical mean value theorem of differential calculus by allowing the use of a Caputo-type fractional derivative instead of the commonly used first-order derivative. Similarly, we generalize the classical mean value theorem for integrals by allowing the corresponding fractional integral, viz. the Riemann-Liouville operator, instead of a classical (firstorder) integral. As an application of the former result we then prove a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 14 publications
(25 reference statements)
2
29
0
Order By: Relevance
“…We would like to point out that very recently some related results to those obtained here appeared in the literature [2,4,5]. Our achievements seem to complement and extend the results within those works.…”
Section: Introductionsupporting
confidence: 88%
“…We would like to point out that very recently some related results to those obtained here appeared in the literature [2,4,5]. Our achievements seem to complement and extend the results within those works.…”
Section: Introductionsupporting
confidence: 88%
“…In the last decades, fractional calculus and fractional differential equations have attracted much attention, we refer to [1,2,9,15,20,21,24,25], and references therein. It is found that many phenomena can be modeled with the help of fractional derivatives or integrals, such as fractional Brownian motion [5], anomalous diffusion [23,30], etc.…”
Section: α T U(t) = Au(t) + F (T U(t)) T ∈ (0 B] U(0) = G(u)mentioning
confidence: 99%
“…Since the Hurst phenomenon amounts to the clus-tering of wet years with wet years and dry years with dry years, the so-called "Joseph effect" from the Bible (Mandelbrot, 1977), it has important consequences on the planning and operation of water storage systems over long periods (Koutsoyiannis, 2005). The Hurst phenomenon in hydrologic flow processes was later demonstrated convincingly by various researchers, including Eltahir (1996), Radziejewski and Kundzewicz (1997), Montanari et al (1997), and Vogel et. al.…”
Section: Introductionmentioning
confidence: 99%